2012
DOI: 10.1371/journal.pone.0035405
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Imaging of Human Atherosclerotic Lesions by Intravascular Electric Impedance Spectroscopy

Abstract: BackgroundNewer techniques are required to identify atherosclerotic lesions that are prone to rupture. Electric impedance spectroscopy (EIS) is able to provide information about the cellular composition of biological tissue. The present study was performed to determine the influence of inflammatory processes in type Va (lipid core, thick fibrous cap) and Vc (abundant fibrous connective tissue while lipid is minimal or even absent) human atherosclerotic lesions on the electrical impedance of these lesions measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…We characterize the stretchable sensors in terms of distinct changes in impedance and phase spectra in response to balloon inflation pressure. Our 2-point approach represents an advancement to the previously proposed linear 4-point electrode arrays 28, 29, 30 , which preclude detection of small and non-homogeneous lesions. Thus, we demonstrate a simplified 2-point electrode configuration to advance the electrochemical impedance measurements for intraplaque lipid-laden lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We characterize the stretchable sensors in terms of distinct changes in impedance and phase spectra in response to balloon inflation pressure. Our 2-point approach represents an advancement to the previously proposed linear 4-point electrode arrays 28, 29, 30 , which preclude detection of small and non-homogeneous lesions. Thus, we demonstrate a simplified 2-point electrode configuration to advance the electrochemical impedance measurements for intraplaque lipid-laden lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, fat tissue is anhydrous and thus, a poor conductor. The high lipid content, including negatively charged active lipids such as oxidized low density lipoprotein (oxLDL) 27 and foam cells present in the plaque change the endoluminal electrochemical properties that can be measured by EIS 17,28,29,30 …”
Section: Introductionmentioning
confidence: 99%
“…(Streitner et al 2012; Streitner et al 2009; Yu et al 2011b; Yu et al 2011c) We and others have established a quantitative correlation between tissue impedance and atherosclerotic lesions in terms of active lipid content (oxLDL). Streiners et al .…”
Section: Discussionmentioning
confidence: 99%
“…deployed impedance sensor by using a linear 4-point electrode configuration into ex vivo human coronary arteries, and demonstrated that inflammatory process in advanced vulnerable plaques (Type V) engendered an elevated tissue impedance. (Streitner et al 2012) However, the linear 4-electrode configuration poses two main constraints: 1) the large size of 4-electode array (1.4mm in the entire length) limits its capability to assess large lesions; and 2) the linear-arrays entails a limited spatial resolution to assess small and non-homogeneous lesions. For these reasons, we proposed the concentric bipolar microelectrodes to provide high spatial resolution (0.5mm diameter) and symmetric tissue impedance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation